Analysis of Factors Related to Pulmonary Nodules in Patients With Fatty Liver: A Large-Scale Cohort Study Based on a Physical Examination Population - Qin Y; Huang X; Lin J; Pan L; Liang Q; Li W (International Journal of General Medicine)
Yan Qin,1,* Xiaozhi Huang,1,* Jiali Lin,2,* Liuxian Pan,1,* Qiuyu Liang,2 Wei Li1 1Health Management Center, People’s Hospital of Guangxi Zhuang Autonomous Region and Guangxi Academy of Medical Sciences, Nanning, People’s Republic of China; 2Health Management Research Institute, People’s Hospital of Guangxi Zhuang Autonomous Region and Guangxi Academy of Medical Sciences, Nanning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Li, Health Management Center, People’s Hospital of Guangxi Zhuang Autonomous Region and Guangxi Academy of Medical Sciences, Nanning, Guangxi, 530021, People’s Republic of China, Email lw6666gx@aliyun.com Qiuyu Liang, Health Management Research Institute, People’s Hospital of Guangxi Zhuang Autonomous Region and Guangxi Academy of Medical Sciences, Nanning, Guangxi, 530021, People’s Republic of China, Email liang_qiu_yu@foxmail.comPurpose: People with fatty liver are at high risk for pulmonary nodules, but the underlying mechanism is unclear. This study aimed to investigate the occurrence of lung nodules in fatty liver patients and explore influencing factors.Patients and Methods: We retrospectively analyzed 57,119 individuals who underwent health checkups at the People’s Hospital of Guangxi from May 2020 to May 2024. Patients with fatty liver were divided into pulmonary nodule and no pulmonary nodule groups. Univariate and multifactorial analyses were conducted using physical examination data, laboratory test indexes, and imaging information. Logistic regression analysis was used to identify independent predictors of pulmonary nodules in fatty liver patients.Results: A total of 20,042 patients with fatty liver were included in the study, with 12,334 (61.5%) in the lung nodule group and 7708 (38.5%) in the non-lung nodule group. Age, gender, systolic and diastolic blood pressure were significantly higher in the pulmonary nodule group, while body weight, waist circumference, hemoglobin, uric acid, and glutamyltransferase were lower. Multifactorial logistic regression analysis showed that male gender, body weight, age, and diastolic blood pressure were significant factors influencing lung nodule development in fatty liver patients.Conclusion: Fatty liver disease is independently associated with an increased incidence of pulmonary nodules, highlighting its importance in lung cancer screening and prevention.Keywords: pulmonary nodules, fatty liver, health checkup, influencing factors, retrospective cohort study